(3aUd GdebGd aj TQM cJGH GdCeKGds - (3YHO Gddg Hf YHO GdYRjR Hf eMeO GdHcQj GdCfOdSj, CHh YHjO,J (B487 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEfj JUaMJ cJGH GdCeKGd dCHj YHjO GdbGSe Hf SdGe, s
(3BNQgG (B:s
(3hjJSGhi QajYge hhVjYge HdZJ s
(3JJab aj BNQgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3fSNI KGfjI? GdChQGb GdChdi hGdCNjQI cJHJ Hbde eZGjQ MOjKkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B75s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B91 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs